GAMBARAN TINGKAT PENGETAHUAN REMAJA TENTANG KEHAMILAN TIDAK DIINGINKAN (UNWANTED PREGNANCY) PADA SISWA MADRASAH ALIYAH MUHAMADYAH 1 BOYOLALI - Musta'in; Resita Aprilia Sandhi; Liss Dyah Dewi Arini (Universitas Duta Bangsa Surakarta, 2022)
Introduction: Unwanted Pregnancy is a condition where the couple does not want the birth process of a pregnancy that can rob them of the pleasures of adolescence. Based on the preliminary study, it was found that 1 student experienced Unwanted Pregnancy, 18 (90%) students did not know about Unwanted Pregnancy, 2 students (10%) knew enough about Unwanted Pregnancy. Objectives: to find out the description of adolescent knowledge about Unwanted Pregnancy at Madrasah aliyah Muhamadyah 1 Boyolali. Methods: The research design is descriptive quantitative, the measuring instrument used is a questionnaire. The research sample was students of Madrasah Aliyah Muhamadyah 1 Boyolali. The sampling technique was proportional random sampling, obtained 68 students, the analysis used was univariate. Result: The level of knowledge of adolescents about Unwanted Pregnancy (Unwanted Pregnancy) respondents had good knowledge, namely 53 people (78%) followed by respondents who had sufficient knowledge, namely 12 people (18%) and respondents who had less knowledge, namely 3 people (4%). Conclusion: The majority of adolescents' knowledge about Unwanted Pregnancy is good. Teenagers are expected to always increase their knowledge about Unwanted Pregnancy so that Unwanted Pregnancy does not occur.